2021
DOI: 10.1016/j.ultsonch.2021.105685
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasonic on the structure and quality characteristics of quinoa protein oxidation aggregates

Abstract: Graphic abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 59 publications
(68 reference statements)
7
55
0
1
Order By: Relevance
“…The content of SH can reflect the degree of protein denaturation and are essential to the functional properties of proteins [44] . The content of free SH increased after sonication, reaching maximum values of 7.1 and 5.1 μmol/g when the ultrasonic power was 150 and the treatment time was 30 min ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The content of SH can reflect the degree of protein denaturation and are essential to the functional properties of proteins [44] . The content of free SH increased after sonication, reaching maximum values of 7.1 and 5.1 μmol/g when the ultrasonic power was 150 and the treatment time was 30 min ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, the aggregation degree of the protein oxidative aggregates is changed and the protein presents good functional features. Cao et al found that ultrasound could modulate the aggregation and conformation of oxidized quinoa proteins by altering intermolecular forces, thereby enhancing the functional features of quinoa proteins [12] . Boora et al found that ultrasonication can improve the emulsification and physicochemical features of whey protein soluble aggregates [2] .…”
Section: Introductionmentioning
confidence: 99%
“…22 Demetra. 2022;17:e56992 EQ = mg de aminoácido/grama de proteína teste mg de aminoácido/grama de proteína padrão A partir dos valores de EQ, calculou-se o valor proteico da quinoa por meio do PDCAAS -Protein Digestibility-Corrected Amino Acid Score, 23 Para o cálculo de CEA, foi utilizada a seguinte fórmula: CEA= ganho de peso do animal (g)/ ingestão total (g).…”
Section: Determinação De Digestibilidade In Vivounclassified